PENGARUH KEAHLIAN AUDIT PADA KUALITAS AUDIT INTERNAL DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL MEDIASI - Narayanti, Ni Nyoman; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2017)
This study aimed to analyze the effect of audit expertise in internal audit quality with good governance as a moderating variable. This research was conducted in all offices PT. Simas Insurance Bali Province nine offices located in Bali region in 2016. The sample was determined by the method of sample saturated by making all respondents auditor as many as 35 people. The data collection is done by distributing questionnaires to 35 respondents. Data analysis techniques in this study using SPSS program that includes: validity and reliability test, classic assumption test, and test this hypothesis using regression analysis techniques moderation. Based on the analysis, the expertise of the auditor's positive effect on the quality of internal audit at PT. Simas Insurance Bali Province. Good governance able to moderate or strengthen the effect of audit expertise on the quality of internal audit at PT. Simas Insurance Bali Province.
Keywords: Skills Audit, Good Governance, Internal Audit Quality